The influence of optical properties of paints and coatings on the efficiency of infrared nondestructive testing applied to aluminum aircraft structures; Infrared Physics & Technology; Vol. 77 - Burleigh D. D. Douglas; Vavilov V. P. Vladimir Platonovich; Pawar S. S. Sachin Sampatrao (2016, 2016)
Title screen